Effect of Problem Based Learning (PBL) on Ability Writing Poetry for Class VII Students of MTs Hizbul Wathan Semaya - Herman Wijaya; Zul Fikri (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aimed to determine the effect of Problem Based Learning (PBL) to the ability in writing poetry of student in class VII MTs. Hizbul Wathan NW Shemaiah year 2018/2019. The method used in this research is the experimental method. This study design using true experimental design. The sampling technique used simple random sampling, VII A class as an experimental class and VII B as the control class. The data analysis technique used to test the hypothesis by using t. After test data analysis, the result for the t count = 2.33 and t table = 2,02 at significance level of 5%. Because t count> t table (2.33> 2.02) so H0 is rejected and Ha accepted which means that learning to use the model of Problem Based Learning is more effective than conventional learning models. Based on the results of hypothesis testing concluded that the use of Problem Based Learning model of proper use by teachers to see the students' ability to write poetry. Quantitative and qualitative results of student  poetry was very satisfying. The learning process is very effective and fun to affect the ability to write poetry of student in class VII MTs. Hizbul Wathan NW Shemaiah Year 2018/2019.